Analisis Permintaan dam Penawaran Lateks Pekat untuk Bahan Baku Pabrik Aspal Karet di Kabupaten Musi Banyuasin - Panggabean, Artha Dwi Natasya (Universitas Bojonegoro, 2024)
The purposes of the research are: (1) To analyze the demand for concentrated latex for rubber farmers who are members of the 5 UPPB Assisted based on the installed power capacity and the real capacity of the Rubber Asphalt Plant in Musi Banyuasin Regency. (2) Analyze the ability of rubber farmers in Sungai Lilin Subdistrict to meet the demand for concentrated latex from the rubber asphalt factory, and (3) Design a balance strategy between the demand and supply of concentrated latex in Musi Banyuasin. This research was conducted in January 2021 at the Rubber Asphalt Factory in Musi Banyuasin Regency and 5 UPPBs assisted in Sungai Lilin District. Data processing methods use demand curve analysis, supply curve analysis and price balance curve analysis. The results showed that the demand curve analysis tends to decrease every month, from March to December which is influenced by the decreasing number of road construction projects. The supply curve analysis shows that the supply of concentrated latex from March to December 2020 tends to increase due to the rising price of concentrated latex and the increasing number of rubber taps each month. In the analysis of the price balance curve, the cut point is obtained at the price of Rp19.428, - This means that it can be said to reach market balance if the price of concentrated latex is Rp.19.428,- The hypothesis put forward by the researcher is in accordance with the results of the study that it is true that the ability of rubber farmers who are members of the 5 UPPB assisted in Sungai Lilin District to meet the needs of the rubber asphalt factory in Musi Banyuasin Regency is bigger than the demand. It can also be interpreted that the quantity of concentrated latex supply is bigger than the demand.